PENERAPAN PENYUSUNAN LAPORAN KEUANGAN PADA USAHA KECIL DAN MENENGAH (UKM) BERBASIS STANDAR AKUNTANSI KEUANGAN ENTITAS MIKRO KECIL DAN MENENGAH DI KOPI BUBUK ADINDA G19 KOTA LUBUKLINGGAU - Khairunnisah Khairunnisah; Eri Triharyati; Yuli Nurhayati (Jurnal Interprof, 2020)
This research is a research in the coffee bean industry business, namely UKM Kopi Powder Adinda G19 Lubuklinggau City which has not implemented the appropriate preparation of financial reports according to the Financial Accounting Standards for Micro, Small and Medium Entities. This study uses data collection methods, by observing and recording directly at the research site (observation), conducting direct question and answer questions at the source (interview), and documentation by reading literature guidelines. This type of qualitative research and data analysis techniques use descriptive qualitative methods. The results of this study indicate that the preparation of the financial statements of the UKM Kopi Powder Adinda G19 Lubuklinggau City is not suitable, only the format of income and expenditure is in the preparation of the financial statements. The recording is still very simple due to the lack of knowledge regarding the preparation of financial reports according to applicable standards so that the Adinda G19 Ground coffee UKM has not been able to produce financial report compilations that are in accordance with the standards.